Effect of prehospital advanced airway management on arterial blood gases in the pragmatic airway resuscitation trial - Grace C. Sullivan; Henry E. Wang; Christopher B. Gage; Jonathan R. Powell; Elisabete Aramendi; Xabier Jaureguibeitia; Andoni Elola; Ahamed Idris; Mohamud R. Daya; Shannon W. Stephens; Jestin N. Carlson; Graham Nichol; et al. (Resuscitation Plus)
Background: Advanced airway devices facilitate ventilation and oxygenation during out-of-hospital cardiac arrest (OHCA). Differences in gas exchange between advanced airway devices are unknown. Objective: Characterize arterial blood gases (ABG) in laryngeal tube (LT) or endotracheal intubation (ETI) cases in the Pragmatic Airway Resuscitation Trial (PART). Methods: We included adult OHCAs with ABG collected ≤ 1.5 h after emergency department (ED) arrival. We collected 1) last prehospital airway technique used 2) ABG measurements (pH, PaO2, PaCO2), and 3) average prehospital end-tidal capnography (EtCO2) values for the last five minutes. We compared airway types, ABG values, and PaCO2-EtCO2 absolute difference (PaCO2-EtCO2) using the Mann-Whitney test, stratifying by circulation status. We also determined prehospital EtCO2 and ED PaCO2 correlation. Results: Of 3004 cases, 401 met inclusion with 272 LT and 129 ETI. Among cases achieving return of spontaneous circulation (ROSC), pH (7.1 vs. 7.2, p = 0.10) and PaO2 (142 vs 170 mmHg, p = 0.08) did not differ. PaCO2 was higher in LT than ETI (58 vs 50 mmHg, p = 0.003). Among cases without ROSC, pH (7.0 vs. 7.0, p = 0.55) and PaCO2 (64 vs. 61 mmHg, p = 0.58) did not differ, but PaO2 was lower in LT than ETI (85 vs. 123 mmHg, p = 0.03). EtCO2 did not correlate with PaCO2 in any airway device/ROSC combination. PaCO2-EtCO2 difference was wider in both LT and ETI non-ROSC cases compared to ROSC cases (27 vs 18 mmHg, p = 0.03). Conclusions: ABG values may vary by prehospital advanced airway management methods. The correlation between EtCO2 and PaCO2 in OHCA patients remains unclear.